Biology and population size of the Golden Parakeet (Guaruba guarouba) in western Pará, Brazil, with recommendations for conservation - Laranjeiras, Thiago Orsi (Revista Brasileira de Ornitologia, 2011)
Golden Parakeets are a poorly known, endangered parrot endemic to the Brazilian Amazon. I describe the flocking patterns, the diet and nest sites of this species and estimate the abundance and size of its population in western Pará. During 2007, I spent about 500 hrs searching for flocks and making transect surveys. Golden Parakeets maintained family flocks of about 10 individuals throughout the year, confirming previous observations. My estimate of reproductive output from the proportion of first year juveniles in the flocks (around 13%) is within the range of estimates found for other parrots, suggesting a normal reproductive output. Feeding bouts (n = 82) confirmed a diversified diet that varies throughout the year, but some items (e.g., Byrsonima spp.; Tapirira guianensis) seem to be more important. All found nest trees were in open areas, adjacent to the continuous forest, exposed to the human disturbance, indicating a potential vulnerability. Surveys indicated that the Golden Parakeet is as common as other sympatric and non-threatened parrots, contrary to expectations. The species probably occupies the whole study region (a strip of about 340 km along the Tapajós river) with an estimated population size of about 500 individuals comprising the largest known population. My data and recent records of the species indicate that its global population size is larger than previously estimated and its official level of endangerment in the red lists should be re-examined.
Biologia e tamanho da população da ararajuba (Guaruba guarouba) no oeste do Pará, Brasil, com recomendações para conservação
Keywords: Abundance; Biological Survey; Bird; Diet; Disturbance; Endangered Species; Endemic Species; Human Activity; Juvenile; Nest Site; Population Size; Red List; Reproductive Productivity; Sympatry; Transect; Vulnerability; Amazonas; Byrsonima; Guaruba Guarouba; Psittacidae; Tapirira Guianensis